Transformation of Jihad education strategies: Overcoming the challenges of Radicalism and Terrorism - Darsimon Darsimon; Al Azhar (International Journal on Advanced Science, Education, and Religion, 2024)
Terrorism is often associated with Islam. As a result, quite a few of those who do not understand Islamic teachings are influenced and see Islam as a religion that is synonymous with violence. One of the things that underlies this view is the concept of jihad. Jihad is considered synonymous with the struggle to take up arms, by spreading terror everywhere. Even though it is contrary to the values ​​of Islamic teachings. Facing this, Muslims must make efforts to rectify and raise awareness among the public about true jihad according to Islamic teachings. This is done through jihad education at both formal and informal levels. Formally, jihad education can be included in one of the learning curricula or lectures, especially in Islamic schools such as Islamic boarding schools, Islamic boarding schools, Tsanawiyah madrasas, Aliyah madrasas, or Islamic higher schools. Meanwhile, informally, an active role and synergy of all components, especially government, academics, ulama, including the mass media, are needed. All lead to the goal of building public awareness about the nature of jihad according to Islamic teachings.